Association Between Baseline Uric Acid and the Risk of Acute Pancreatitis: A Prospective Cohort Study. Issue 8 (September 2022) - Su, Afang; Yuan, Xiaojie; Zhu, Guoling; Jiang, Xiaozhong; Shu, Rong; Yang, Wenhao; Wu, Shouling; Chen, Shuohua; Wang, Li; Cui, Liufu
Abstract : Objectives: The aim of the study is explore the association between serum uric acid (UA) and acute pancreatitis (AP) risk in a Chinese population. Methods: We included 124, 316 participants who enrolled in the Kailuan cohort from 2006 to 2009. We fitted Cox models to estimate the correlation between UA and AP. Result: During an average follow-up of 11.97 years (standard deviation, 2.16 years), 396 AP developed. The incidence rates from quartile 1 to quartile 4 of AP were 20.76, 18.78, 30.58, and 36.79 per 100, 000 person-years, respectively. Multivariate analysis showed a significantly increased risk in quartile 3 (hazard ratio [HR], 1.42; 95% confidence interval [CI], 1.05–1.91) and quartile 4 (HR, 1.61; 95% CI, 1.19–2.17) compared with quartile 1. The association may be modified by alcohol use ( P for interaction = 0.017). The quartile 4 group with excessive alcohol consumption showed an enormously increased risk of AP (HR, 9.09; 95% CI, 1.18–70.21) than those without (HR, 1.46; 95% CI, 1.07–2.00). Conclusions: Elevated serum UA is an independent risk factor for AP. Surveillance of serum UA, especially among heavy drinkers, may be helpful for AP prevention.